The Effect of Motivation, Discipline, and Satisfaction on Employee’s Performance: PT Bank Sinarmas Palembang City - Pratama, M. Yogie Agustian; Moelyati, Trisniarty Adjeng; Tobari, Tobari (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This research aims to determine the influence of work motivation, discipline, and job satisfaction on employee performance at PT Bank Sinarmas in Palembang City. This type of research is associative. Researchers use motivation, discipline, employee satisfaction, and performance variables. The sample in this research is employees of PT. Bank Sinarmas, Palembang City, totaling 86 people, was selected using Cluster Random Sampling. The primary data used in this research was collected through a questionnaire. The data analysis technique used is Multiple Linear Regression with the SPSS Program Application. This research shows that (1) Work Motivation, Discipline, and Job Satisfaction significantly affect employee performance. (2) Motivation has a positive and significant effect on employee performance, (3) Discipline has a positive and significant effect on employee performance, and (4) Satisfaction has a positive but not significant effect on employee performance at PT. Bank Sinarmas in Palembang City